Development controller for 2 axis mechanism machine - Muhammad Hayyul, Sohaimi (2012)
In engineering application most of part is machining to make it realize, an example plastic product. Moulds are machine by using Milling machine, turning machine and EDM machine. This entire machine is using a same concept that was 2 axis mechanisms to move the table. This thesis is focus on controlling stepper motor in axis during machining process in term of positioning motion control. All of the task would be control by using Visual Basic Programming. This project is limited to low cost automation and low servo speed. The device or 3 axis machine has been develop before this, this machine are using stepper motor to move the table, this is because step motor provides efficiently and precise movement that required during application in machining. During this development of controller there are no manufacturer product catalogues, outlining characteristic and rating of actuators that can helps engineer. However, because of lack information, engineers resolve to choose based an experience. From this project, the criteria in the selection aid focus in type of nature of control requirement by the application such as position control, speed control and torque control requirement.